Cyclic behavior of an energy dissipation system with the vertical steel panel flexural-yielding dampers. (November 2022) - Rousta, Ali Mohammad; Gorji Azandariani, Mojtaba; Safaei Ardakani, Masoud Amin; Shoja, Sohrab
Abstract: In this study, an energy dissipation system of the vertical steel panel flexural-yielding dampers (VSPFYDs) system is provided and investigated using a numerical method. The aim of this study is to provide an energy absorption system to improve the hysteresis behavior and performance of steel slit dampers (SSDs). Hence, two types of VSPFYDs and SSDs systems with connection details are provided and developed numerical models for parametric study. Extensive parametric studies have been performed to evaluate and compare the proposed damper (VSPFYDs) with traditional SSDs. To evaluate the proposed dampers, the nonlinear finite element models were developed to predict the hysteretic behavior of VSPFYDs and SSDs using ABAQUS software and ultimately validated with the results of several test specimens. To evaluate the results of this study, a comparison is performed between the seismic parameters of SSDs and VSPFYDs. The results show that the vertical steel panel flexural-yielding dampers increase the seismic parameters compared to the steel slit dampers. Also, the results showed both VSPFYDs and SSDs showed flexural behavior. Finally, the stiffness degradation of dampers was investigated and found that the smallest VSPFYD with a height of 15 cm has the best performance in many aspects. Also, the results show that the details of the construction of the plate connections considerably affected the performance and hysteresis behavior of the VSPFYDs compared to SSDs.